"Four Bright Coins Shining at Me": Financial Education in Childhood, Financial Confidence in Adulthood. Issue 2 (17th June 2018) - Sansone, Dario; Rossi, Mariacristina; Fornero, Elsa
Abstract : We analyze the relation between receiving an allowance (pocket money) in childhood and financial confidence in adulthood. We measure this confidence using self‐reported financial knowledge. Our empirical exercise is based on information provided by a Dutch survey carried out in 2015. We compute our estimates by controlling for parental attitudes and by using a "within‐family" fixed effect model. The results are robust and suggest a long‐lasting effect of pocket money as an easily implementable and informal educational vehicle to help children acquire basic financial concepts and develop good habits, such as budgeting.